The Relationship between Knowledge and Practice on The COVID-19 Prevention of Undergraduate Nursing Program of STIKES Muhammadiyah Gombong - Mulyawati, Rizki Tri; Septiwi, Cahyu; Santoso, Dadi (Prosiding University Research Colloquium, 2022)
Background : The countries worldwide have the same health problems and focus on the COVID-19. The number of cases day to day is increasing significantly. Objective : to identify the relationship between knowledge and practice on the COVID-19 prevention of undergraduate nursing program of STIKES Muhammadiyah Gombong Method : This study was quatitative design with cross-sectional approach. Eighty-eight respondents were taken by random sampling technique and questinnaire was distributed by Google Form then analyzed using Ranks Spearman. Results : data analysis showed that forty-six respondents were in in a moderate knowledge category (52,3%). At the same time, the practice on the COVID-19 prevention showed ttaht fifty-six respondents (63,6%) were in the good practice category. The Rank Spearman test showed a relationship between knowledge and practice on thhe COVID-19 prevention (p-value =0.008). Conclusion : There was a relationship between knowledge and practice on the COVID-19 prevention of undergraduate nursing program of STIKES Muhammdiyah Gombong.